Analysis of Knowledge of Hospital Manager about Occupational Tuberculosis and Associated Factors - Prasetyo, Aditya Agung; Wibowo, Suryo; Ilyas, Muhammad; Fuady, Ahmad; Taufik, Feni Fitriani (UI Scholars Hub, 2024)
Introduction.Knowledge of hospital managers about occupational tuberculosis can affect occupational tuberculosis services in the hospital. This study aims was to identify associated factors with knowledge of hospital manager about occupational tuberculosis in order to improve occupational tuberculosis services in hospitals as seen in the four management functions. Method.Concurrent embedded mixed approaches are used in this cross-sectional study. Focus group discussions (FGD) are used in qualitative research, whereas questionnaires are used in quantitative research. The questionnaire was evaluated using the difficulty level and discriminating index tests. The ten questions were examined both univariate and bivariate. Thematic analysis was used to analyze qualitative research. The quantitative and qualitative data were then integrated. Result.Age and years of service are related to question about definition of occupational diseases and occupational diseases regulation. Education level, occupational health training, and managed occupational disease are related to question about reporting occupational tuberculosis cases. Educational background is related to question about time reporting occupational tuberculosis. Four questions have a correct response frequency of less than 50%, while six questions have a correct answer frequency greater than 50%. Conclusion.No important factor affects knowledge of hospital managers about occupational tuberculosis. Hospital managers require occupational health training to understand occupational tuberculosis.